Introduction to the article collection 'Translation in healthcare: ethical, legal, and social implications'. Issue 1 (December 2016) - Morrison, Michael; Dickenson, Donna; Lee, Sandra
Abstract New technologies are transforming and reconfiguring the boundaries between patients, research participants and consumers, between research and clinical practice, and between public and private domains. From personalised medicine to big data and social media, these platforms facilitate new kinds of interactions, challenge longstanding understandings of privacy and consent, and raise fundamental questions about how the translational patient pathway should be organised. This editorial introduces the cross-journal article collection "Translation in healthcare: ethical, legal, and social implications", briefly outlining the genesis of the collection in the 2015 Translation in healthcare conference in Oxford, UK and providing an introduction to the contemporary ethical challenges of translational research in biology and medicine accompanied by a summary of the papers included in this collection.